Editorial - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Feijoo, Ana Maria Lopez Calvo de; Mancebo, Deise; Mendes, Deise Maria Leal Fernandes; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2012)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Ana Maria Lopez Calvo de Feijoo, Deise Mancebo, Deise Maria Leal Fernandes Mendes, Rita Maria Manso de Barros